2019
DOI: 10.1371/journal.pone.0214913
|View full text |Cite
|
Sign up to set email alerts
|

“We also communicate through a book in the diaper bag”—Separated parents´ ways to coparent and promote adaptation of their 1-4 year olds in equal joint physical custody

Abstract: Joint physical custody (JPC) refers to a practice where children with separated parents share their time between the parents’ respective homes. Studies on parents’ views of JPC for young children are scarce. The aim of this interview study was to explore parents’ perceptions on how they experience and practice equally shared JPC for their 1–4 year-olds in Sweden. Forty-six parents (18 fathers and 28 mothers) of 50 children (31 boys and 19 girls) under 5 years of age were interviewed. Parents were recruited thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
4
0
2
Order By: Relevance
“… 26 For young children’s mental health, positive parenting practices and high quality in the parent–child relations are particularly important and the interviewed parents described improved parent-child relationships and increased satisfaction in parenting after their divorce. 26 27 JPC allowed them to focus entirely on the child when together and they could make decision without having to compromise with a coparent. In a previous study of 3–5 years old, we found no differences in parent reported child mental health between JPC and intact families but could then not include information on coparenting quality or parental conflict.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 26 For young children’s mental health, positive parenting practices and high quality in the parent–child relations are particularly important and the interviewed parents described improved parent-child relationships and increased satisfaction in parenting after their divorce. 26 27 JPC allowed them to focus entirely on the child when together and they could make decision without having to compromise with a coparent. In a previous study of 3–5 years old, we found no differences in parent reported child mental health between JPC and intact families but could then not include information on coparenting quality or parental conflict.…”
Section: Discussionmentioning
confidence: 98%
“…25 A potential explanation for the positive outcome for children in JPC may however be the positive prerequisites for parenting involved in this living arrangement, as described by parents of 1-4 years old in JPC in an interview study. 26 For young children's mental health, positive parenting practices and high quality in the parent-child relations are particularly important and the interviewed parents described improved parent-child relationships and increased satisfaction in parenting Open access after their divorce. 26 27 JPC allowed them to focus entirely on the child when together and they could make decision without having to compromise with a coparent.…”
Section: The Findings In Relation To Coparenting Qualitymentioning
confidence: 99%
“…In addition, a good parent-child relationship depends on the proper upbringing of the children by the parents, adequate love exchanges between the parents and the children, and good communication between them. That is, the three dimensions of parent-child mutual care, love, and communication between parents and their children can be used as indicators of the parent-child relationship (Bergström et al, 2019;Scott et al, 2019). According to the comprehensive literature, it is obvious that parent-child relationships and their interactions have a pivotal impact on children's growth and the shaping of their personality.…”
Section: Parent-child Relationshipsmentioning
confidence: 99%
“…39,167 Parents also in general appear pleased with the arrangement, unless ongoing conflicts are present. 168 parenting by one parent by strong parenting from the other parent, in times of stress. [41][42][43]124 It is important to note that the differences between children and youth in JPC compared to other post-divorce family structures are generally small.…”
Section: Joint Physical Custodymentioning
confidence: 99%